RESEARCH OF THE PHYSICAL PROPERTIES OF DIESEL FUEL-HYDROGEN MIXTURES - Leybovych , Lev; Dymo , Borys; Anastasenko , Sergey; Yevstigneyev , Yurii (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2021)
The change in the viscosity of diesel fuel with dissolved hydrogen, the rate of dissolution of hydrogen in the diesel fuel, and the hydrogen diffusion coefficient in diesel fuel were experimentally determined. Dissolving hydrogen in liquid fuel changes its physical-chemical properties. It has been found that the viscosity and density of diesel fuel change little when it is saturated with hydrogen. The flashpoint in a closed crucible is reduced by 3–4 °C. The rate of dissolution of hydrogen in diesel fuel has been investigated. It has been found that the diffusion coefficient of hydrogen in diesel fuel depends significantly on the initial concentration of H2 in the fuel. The liquid fuel is advisable to supply with saturated hydrogen for the safety of the heat engine operation. The design of the hydrogen fuel saturation system with a special hydrogen sensor based on the MQ-8 sensor was proposed. The system of protection of the research stand from unauthorized emissions of hydrogen into the environment has been worked out. The protection ensures the shutdown of the stand equipment when the hydrogen concentration in the zone of its generation and supply to the fuel is at the level of 1%.